Kinetics of the Active Medium of a Copper Vapor Brightness Amplifier - Kulagin A. E. Anton Evgenievich; Torgaev S. N. Stanislav Nikolaevich; Evtushenko G. S. Gennady Sergeevich; Trigub M. V. Maksim Viktorovich (2018, 2018)
Title screen